2019
DOI: 10.1021/acs.orglett.9b01622
|View full text |Cite
|
Sign up to set email alerts
|

Diborative Reduction of Alkynes to 1,2-Diboryl-1,2-Dimetalloalkanes: Its Application for the Synthesis of Diverse 1,2-Bis(boronate)s

Abstract: Reduction of alkynes with alkali metals in the presence of B 2 pin 2 results in diboration of alkynes. Distinct from conventional dissolving metal hydrogenations, two carbon−boron bonds and also two carbon−alkali metal bonds can be constructed in one operation to form 1,2diboryl-1,2-dimetalloalkanes. The 1,2-diboryl-1,2-dimetalloalkanes generated are readily convertible to a wide range of vicinal bis(boronate)s. In particular, oxidation of the 1,2dianionic species provides (E)-1,2-diborylalkenes, unique antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Diarylalkynes containing a thiophene ring also provided the desired products in high yields (2t-x). When a strong electron-withdrawing group is present on the para-position of the benzene ring, the boron in the benzyl group is unstable and is easily protonated [8,10,20]. This issue was encountered herein, and after many attempts (see Supplementary materials (online) for unsuccessful substrates), it was surprisingly found that 2y could be obtained in medium yield (35%) under the present conditions, though the Ac group on the meta-position of the benzene ring.…”
Section: Extension Of Substrate Scopementioning
confidence: 71%
See 1 more Smart Citation
“…Diarylalkynes containing a thiophene ring also provided the desired products in high yields (2t-x). When a strong electron-withdrawing group is present on the para-position of the benzene ring, the boron in the benzyl group is unstable and is easily protonated [8,10,20]. This issue was encountered herein, and after many attempts (see Supplementary materials (online) for unsuccessful substrates), it was surprisingly found that 2y could be obtained in medium yield (35%) under the present conditions, though the Ac group on the meta-position of the benzene ring.…”
Section: Extension Of Substrate Scopementioning
confidence: 71%
“…In 2017, our group [9] developed a base-controlled highly selective protocol for the synthesis of vicinal diboronates from terminal alkyl alkynes via domino-borylation-protodeboronation (DBP) with stoichiometric base (Scheme 1c). In 2019, Yorimitsu's group [20] developed a technique for the diborative reduction of alkynes to 1,2-bisboronates (a mixture of threo-and erythro-configuration) with the alkali metal sodium in two steps (Scheme 1d). Vicinal diboronates are potentially effective intermediates for the construction of polyarylethanes and vicinal diols.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have been interested in the development of reductive transformations using diboron reagents . During our investigation, we found that sulfoxides were reduced to the corresponding sulfides by means of diborons.…”
Section: Methodsmentioning
confidence: 89%
“…More recently, Nogi and Yorimitsu have developed the diborative reduction of alkynes towards 1,4‐diboratabutadiene dianions 15 , by means of B 2 pin 2 and alkali metals (Scheme 12). [27] A possible reaction mechanism has been suggested by the authors considering that the electron reduction of the alkyne would generate radical anion that further react with B 2 pin 2 to form borate intermediates.…”
Section: Synthesis Of α‐Monoboryl Carbanions/borata‐alkenesmentioning
confidence: 99%